2011
DOI: 10.1007/s10344-011-0514-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological and virological survey and resighting of marked wild geese in Germany

Abstract: In order to investigate the potential role of arctic geese in the epidemiology, the spatial and temporal spread of selected avian diseases,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…By comparing our serological results with results from previous studies on other geese species, we found differences in the seroprevalence of IAV, AAvV-1, and EDSV between different species (Table 4). Native European migratory species, e.g., greater white-fronted goose (Anser albifrons), seem to be more exposed to IAV showing mean seroprevalence of 10.6% (Kruckenberg et al 2011) compared to neozootic resident species, such as Egyptian and Canadian geese (Branta canadensis) which show 6.1% and 2.8% seroprevalences, respectively (this study, Bönner et al 2003). Similar trends can be observed also in case of AAvV-1 (Table 4).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…By comparing our serological results with results from previous studies on other geese species, we found differences in the seroprevalence of IAV, AAvV-1, and EDSV between different species (Table 4). Native European migratory species, e.g., greater white-fronted goose (Anser albifrons), seem to be more exposed to IAV showing mean seroprevalence of 10.6% (Kruckenberg et al 2011) compared to neozootic resident species, such as Egyptian and Canadian geese (Branta canadensis) which show 6.1% and 2.8% seroprevalences, respectively (this study, Bönner et al 2003). Similar trends can be observed also in case of AAvV-1 (Table 4).…”
Section: Discussionsupporting
confidence: 79%
“…In line with this, AAvV-1 seroprevalence in greater white-fronted goose shows clear seasonal variation (Table 4). Molecular results from a previous study in Germany revealed a prevalence of 13.8% (4/29) for AAvV-1 in Canada geese during molt in autumn and of 1.6% (2/128) in white-fronted geese in winter (Kruckenberg et al 2011). Another RT-PCR-based study by (Fouchier et al 2003) reported a prevalence of 1.4% for IAV in wild geese (i.e., white-fronted, greylag (A. anser) and brent goose (Branta bernicla) ratio 20/1387) and of 2.6% in wild ducks (i.e., widgeon (Anas penelope), mallard (A. platyrhynchos), shoveler (A. clypeata), and teal (A. crecca) ratio 57/2232) on wintering grounds in northern Europe.…”
Section: Discussionmentioning
confidence: 80%
“…1800 samples from Ukraine from all seasons (mute swan Cygnus olor , whooper swan Cygnus cygnus , greater white-fronted goose Anser albifrons , greylag goose Anser anser , and red-breasted goose Branta ruficollis ), but were able to isolate APMV-1 only in two greater white-fronted geese sampled in winter. German studies based on serology report either negative results (greylag goose [ 23 ]), 6–8% seroprevalence in breeding Canada geese Branta canadensis ,[ 24 ] 14% in Canada geese in fall,[ 25 ] and 45% in greater white-fronted geese in October. [ 20 ] The only studies from the Nordic countries did not find any APMV-1 antibodies in greylag geese (Norway, spring [ 26 ] and Finland, fall [ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
“…As stated above, Newcastle disease is not of immediate human health concern, but the role of swans and geese as reservoir or spill-over hosts [ 21 , 30 ] and their potential to act as long-distance biological or mechanical vectors [ 22 , 25 , 31 ] of precursors to velogenic APMV-1 strains remains poorly understood, and warrants continued attention ( cf . [ 32 34 ]) from a poultry health perspective.…”
Section: Resultsmentioning
confidence: 99%